IL-21 signaling promotes the establishment of KSHV infection in human tonsil lymphocytes by increasing differentiation and targeting of plasma cells - Alomari, Nedaa; Totonchy, Jennifer (Frontiers in Immunology, 2022)
Factors influencing Kaposi’s sarcoma-associated herpesvirus (KSHV) transmission and the early stages of KSHV infection in the human immune system remain poorly characterized. KSHV is known to extensively manipulate the host immune system and the cytokine milieu, and cytokines are known to influence the progression of KSHV-associated diseases. Here, using our unique model of KSHV infection in tonsil lymphocytes, we investigate the influence of host cytokines on the establishment of KSHV infection in human B cells. Our previous work identified the early targeting of plasma cells for KSHV infection. In this study, we examine whether IL-21, a cytokine known to profoundly influence plasma cell fate, influences the early stages of KSHV infection in B lymphocytes. We show that IL-21 signaling promotes KSHV infection by promoting both total plasma cell numbers and increasing KSHV infection in plasma cells as early as 3 days post-infection. We further demonstrate that the synergistic effect of KSHV infection and IL-21 treatment on plasma cell frequencies is due to differentiation of new plasma cells from naïve B cell precursors. We examine T cells secreting IL-21 in our tonsil specimens and determine that IL-21 producing CD8+ central memory T cells are correlated with plasma cell frequencies and KSHV targeting of plasma cells. These results demonstrate the novel finding that differentiation of new plasma cells is involved in the early stages of KSHV infection in B cells, and that IL-21 signaling can potentiate this effect thereby increasing the overall magnitude of KSHV infection at early timepoints. These results suggest that IL-21 signaling represents a host-level susceptibility factor for the establishment of KSHV infection.